Management strategies for achalasia. Issue 9 (September 2014) - Vela, M. F.
Abstract Treatment options for achalasia include oral pharmacologic therapy, endoscopic injection of botulinum toxin, pneumatic dilation, and myotomy (conventionally by laparoscopy, but more recently by an endoscopic approach). Oral pharmacologic agents have fallen out of use because of insufficient efficacy and frequent side effects. Endoscopic injection of botulinum toxin is safe and has good short‐term effectiveness, but as the effect invariably wears off after a few months, this treatment is reserved for patients who are not candidates for more definitive treatments. Pneumatic dilation and surgical myotomy are currently considered the most effective treatments, with similar effectiveness in randomized controlled trials with follow‐up of up to 2 years. The risk/benefit ratio and choice of therapy depend on patient characteristics (age, comorbidities, disease stage, prior treatments), patient's preference, and locally available expertise. Treatment of patients who fail or relapse after initial therapy is challenging and the success rate of pneumatic dilation or myotomy in this group is lower compared with previously untreated patients. The recently developed peroral endoscopic approach to myotomy has achieved excellent results in early uncontrolled studies, but high‐quality randomized trials are needed to ensure widespread adoption is reasonable. Finally, retrospective data suggest that achalasia subtypes as defined by high‐resolution esophageal pressure topography may guide treatment choice, but confirmation in prospective outcome studies is awaited.